Juegos serios para la rehabilitación física de pacientes. Patología: ataxia (2016)
In this book an alternative for the treatment of ataxia (a disease that affects coordination and body strength) based on a set of games augmented reality that would allow patients develop a series of exercises without the need to travel to centers presents specialized, thus reaching a larger segment creating a progress against the disease, since a greater number of therapies better quality of life of the individual and additionally generates a democratization of those suffering from this disease, aiming to reach the ultimate goal the easy access to health as fundamental right of civil society.